Digital Multicultural Da’wah and the Prevention of Virtual Radicalism Among Generation Z - Wijaya, M. Febriyanto Firman; Al Afnan, Ahmad Ghozi (Prodi Studi Agama-Agama, 2025)
The rapid spread of radical ideologies through digital platforms has made Generation Z a primary target of virtual radicalism. As digital natives, they are highly exposed to online content, increasing their vulnerability to extremist narratives. This study explores the role of multicultural da’wah as a preventive strategy against virtual radicalism among Generation Z. Employing a thematic literature review, this research analyzes recent scholarly works, reports, and other relevant sources. The study focuses on the conceptual framework and practical implementation of multicultural da’wah, particularly its adaptation in digital contexts. Findings show that multicultural da’wah offers an inclusive approach grounded in tolerance, cultural diversity, and interfaith dialogue. It is effectively implemented through creative digital campaigns, educational applications, culturally-rooted content, and community-based programs. Key success factors include emotional resonance with youth, digital literacy, psychological sensitivity, and collaboration across religious, educational, and governmental institutions.